2005
DOI: 10.1111/j.1365-3148.2005.00609.x
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of pathogen inactivation for platelet transfusions in the Netherlands

Abstract: The objective of this study is to estimate cost-effectiveness of pathogen inactivation for platelet transfusions in the Netherlands. We used decision tree analysis to evaluate the cost-effectiveness of the addition of pathogen inactivation of pooled platelets to standard procedures for platelet transfusion safety (such as, donor recruitment and screening). Data on transfusions were derived from the University Medical Centre Groningen (the Netherlands) for 1997. Characteristics of platelet recipients (patient g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 42 publications
0
22
0
1
Order By: Relevance
“…IPF transfusion needs further investigation to establish the social and economic cost, but the benefits of using IPF solutions include reduction in the severity of hematologic disease and related complications, such as intravascular coagulation during PBSC transplantation in children and young patients, and the frequency of minor side effects including mucosal hemorrhage 2629. The higher cost to carry out “dedicated” PLT apheresis and the purchase of a modern hemocytometer for quantifying the IPF, is offset by the savings in health and medical support for post-transplantation complications.…”
Section: Resultsmentioning
confidence: 99%
“…IPF transfusion needs further investigation to establish the social and economic cost, but the benefits of using IPF solutions include reduction in the severity of hematologic disease and related complications, such as intravascular coagulation during PBSC transplantation in children and young patients, and the frequency of minor side effects including mucosal hemorrhage 2629. The higher cost to carry out “dedicated” PLT apheresis and the purchase of a modern hemocytometer for quantifying the IPF, is offset by the savings in health and medical support for post-transplantation complications.…”
Section: Resultsmentioning
confidence: 99%
“…This may be interpreted as underutilizing the protective potential of PRT. ii) In addition, we did not model the potential of PRT to reduce the possibility of adverse events to zero as has been done in previous analyses [23,24]. While other reports have demonstrated 1.5-6 log/ml reductions in the presence of infectious agents using Mirasol [26], we have modeled roughly 1-2 log reductions.…”
Section: Discussionmentioning
confidence: 99%
“…The study authors concluded that, in view of the relatively high (and internationally accepted) net costs per LYG for blood transfusion safety interventions, the data generated by this model indicate that pathogen inactivation may be cost-effective. However, the study made the assumption that the pathogen inactivation method would be 100% effective, rendering this result uncertain [125]. In Germany (for example), approximately 20 million € (50 € (assumed price) for amotosalen/UVA treatment for 400,000 PC) would have to be paid in order to prevent 6 instances of TTBI [9].…”
Section: Cost Considerationsmentioning
confidence: 99%